THE APPLICATION OF BIBLIOTHERAPY THROUGH WATTPAD IN ISLAMIC-BASED COGNITIVE COUNSELING SERVICE TO MAINTAIN MENTAL HEALTH - KHILMAN ROFI’AZMI; MELLIA IRAWATI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
There are several approaches to changing a person's behavior such as using the media of Bibliotherapy. Bibliotherapy is a medium that defines the use of literature and poetry to treat people with ego and mental illnesses. This study aims to determine students' understanding of mental health and the effectiveness of students using the Wattpad media. The approach used is Research and Development (R&D). data collection tool using questionnaires, observations and documentation. From the results of the study, it can be concluded that the use of Bibliotherapy using "Wattpad" media with cognitive counseling services for students is declared feasible to use.  After conducting field trials, the researchers tested the effectiveness of students with a t-test in which the t-test results were significant. The results of the trial on students received good responses to the use of Wattpad-based mental health novel facilities to maintain students' mental health. Suggestions from the results of this research are expected to add insight to knowledge related to mental health around us and the factors that influence it.